Perspectives of Engineered Marine Derived Polymers for Biomedical Nanoparticles - Thi My Tran, Khanh; Van Vo, Toi; Duan, Wei; Ha-Lien Tran, Phuong; Truong-Dinh Tran, Thao (Current Pharmaceutical Design, 2016)
Marine environment exhibits an enormous diversity of organisms which contains an abundant source of polysaccharides. As polymer matrix carriers, marine-based polymers possess several valuable properties including high stability, non-toxicity, hydrophilicity, biodegradability, with low production cost. Despite notable biological activities of these natural polymers, there are certain limitations in exploring their functions in applications of nano-sized drug delivery systems. The review aims to demonstrate exceptional characteristics of marine-based polymers including fucoidan, alginate, carrageenan, hyaluronic acid, chondroitin sulfate, and chitosan as well as provide perspectives of current publications on their nanoparticle formulations for biomedical applications.
Keywords: drug delivery